Current Concepts in Rectal Cancer - Fleshman, James W.; Smallwood, Nathan (Clinics in Colon and Rectal Surgery, 2015)
The history of rectal cancer management informs current therapy and points us in the direction of future improvements. Multidisciplinary team management of rectal cancer will move us to personalized treatment for individuals with rectal cancer in all stages.
Keywords: colon and rectum; colorectal disease; neoadjuvant therapy; multidisciplinary